Mechanical And Morphological Properties Of Polylactic Acid- Poly(Hydroxybutyrate-Cohydroxyhexanoate) Blends-Effect Of Blends Ratio And Maleated Compatibilizer - Roslan, Abdul Rahman (Universiti Sains Malaysia, 2017)
This research was conducted to investigate the optimum of PLA/PHBHH blends on mechanical properties, the effect of blends ratio and the effect of maleated compatibilizer. The PLA/PHBHH were prepared by internal mixer. The blend ratio of 100/0, 75/25, 50/50, 25/75 and 0/100 were prepared. The optimum blend ratio of PLA/PHBHH on tensile properties is about 75PLA/25PHBHH with 42.46 MPa. The tensile strength of the blends decreases with addition of PHBHH blend ratio so as the modulus. The increment of PHBHH composition that having higher ductility improve the brittleness of PLA. For the fracture toughness testing, 75/25 blend ratio having higher fracture toughness value at 2.99 MPa.m0.5. The addition of PLA-g-MA compatibilizer were studied for 75/25, 50/50 and 25/75 blends ratio. It was found that compatibilizer improved the tensile and fracture toughness properties of the polymer blend. The results can be supported by morphological observation. From FESEM results obtained, it was seen that the compatibilizer improve the phase adhesion of PLA and PHBHH that gives impact on the mechanical properties of the blends. Therefore, PLA-g-MA compatibilizer enhanced the compatibility of PLA/PHBHH blends.